O espaço da morte em Venha ver o pôr do sol, de Lygia Fagundes Telles e A tumba, de Howard Phillips Lovecraft - Melo, Alice Vasconcelos (2022)
This research constitutes a topoanalytic study of the character's sentimental relationship through the topos of death in the short stories Venha Ver o Pôr do Sol (1970), by Lygia Fagundes Telles (2009), and A Tumba (1922), by Howard Phillips Lovecraft (2019). It is dedicated to analyze the sentimental relationship of the protagonists with the space of death represented by the setting of each narrative. It is assumed that the character's feeling of affection or aversion for the space is conditioned on his direct and intimate experience with the topos, the topophilic feeling being determined by familiarity with the place, and the topophobic feeling triggered by strangeness to the place. To support this research, the conceptions of Borges Filho (2007), Brandão (2013), Lins (1976) and Dimas (1987) on the fictional space were employed. Regarding topopathy, the topophilic and topophobic feelings, the foundations of Borges Filho (2007) and Tuan (1980 and 2005) were used. Still about the conceptions of sepulchral spaces, the support is in the conceptions of Foucault (2013) and Lauwers (2015). The analysis of the short stories is based on the spatial path taken by the protagonists, in order to verify the space perceived and experienced from the sensory gradients and the spatial coordinates. It is found that the sentimental relationship of affection or aversion of the character by the space of death are the result of direct experience with the topos, which are conditioned to the ties of familiarity or strangeness with the place occupied and perceived by each character